Gardenia: characteristics, uses, pests and diseases and basic aspects of its cultivation - Castilla-Valdés, Yanelis (Agronomía Mesoamericana, 2018)
The gardenia (Gardenia jasminoides Ellis) is a plant that is very appreciated in gardening for the beauty and fragrance of its flowers, attractive size and the intense green color of the foliage. In contrast to its ornamental qualities, it is not one of the most used plants in Cuba and other countries, so it is necessary to promote its cultivation. The present review objective was deepening and integrating information regarding the characteristics, utility, main pests and diseases and methods of propagation of the gardenia. The sunny and warm conditions during the day and fresh at night, relative humidity upper than 60% and acid soil, rich in iron, are favorable for this species development. Between the lesser known properties of gardenia, there are the medicinal ones because its extracts have diverse pharmacological effects. Its most common diseases are of fungal origin and provoke the rot roots and foliar spots. Among the pests that have the greatest incidence stand out the insects (aphids, citrus whitefly, coccids, and thrips). Gardenia plants can be propagated by different traditional methods (seeds, air layering, cuttings, and grafting), but the application of in vitro cultivation techniques are an efficient way to achieve this purpose, since it allows accelerated multiplication and production of healthy plants, also, it constitutes an alternative for obtaining secondary metabolites with pharmaceutical properties.